PT. Indosurya Finance Solo Baru Employee Management Information System Analysis - Ika Srirahayu; Isnawati Muslihah (Institut Teknologi Bisnis AAS Indonesia, 2021)
Attendance is an important factor in maintaining the quality of an employee's performance in a company. With technological advances such as nowadays, the ease of attendance can also be carried out easily, the use of the old attendance system is also considered less effective in today's era, employees need efficiency in the absent process, as implemented by Indosurya Finance's Solo Baru branch which has left the old system attendance , where the previous abscess system used the signature system, the block card system, and the fingerprint system. In this old system, the majority of employees worked not only in the office having difficulty meeting clients outside the office at any time, because they had to come to the office if they wanted to be absent. Therefore the company replaced it with a new system, namely using an application called Great Day HR. With a modern employee attendance system like this, it can help companies make arrangements for existing human resources and the purpose of this research is to determine the feasibility of an attendance system using Great Day HR for the future. The method in this research is through observation, interview, documentation, and literature study. The system design is made with context diagrams, HIPO, DAD, input output design, hardware requirements analysis, software requirements analysis. By using this online attendance system employees can perform attendance efficiently and effectively according to the needs of each employee. The final result of this online attendance system is an attendance recap data from each user owned by Indosurya Finance employees.